Serum osteocalcin levels in patients with nonalcoholic fatty liver disease: Association with ballooning degeneration - EREN, FATİH; YILMAZ, YUSUF (INFORMA HEALTHCARE, 2011)
Our aim was to examine the relation of serum osteocalcin (OCN) levels with the clinical, biochemical, and histological characteristics of patients with biopsy-proven nonalcoholic fatty liver disease (NAFLD). We carried out a case-control study including 99 patients with biopsy-proven NAFLD and 75 age-and sex-matched controls. Concentrations of OCN were measured in aprotinin-treated serum samples using a solid-phase enzyme amplified sensitivity immunoassay. Serum OCN levels were significantly lower in patients with NAFLD than in healthy controls. In patients with NAFLD, serum OCN levels were inversely associated with ALT (r = -0.36, p < 0.001), AST (r = -0.39, p < 0.001), HOMA-IR (r = -0.30, p < 0.01) and the degree of hepatocyte ballooning (r = -0.20, p < 0.05). Serum OCN was the only independent predictor of the degree of hepatocyte ballooning in NAFLD patients (beta = -0.24; t = -2.146, p < 0.05). Compared with controls, NAFLD patients have a decrease in serum OCN concentrations, which is significantly associated with serum transaminases and the extent of hepatocyte ballooning.
Keywords: Osteocalcin; nonalcoholic fatty liver disease; hepatocyte ballooning; METABOLIC SYNDROME; INSULIN-RESISTANCE; STEATOHEPATITIS; SECRETION; GLUCOSE; MEN